Development of a new portable X-ray powder diffractometer and its demonstration to on-site analysis of two selected old master paintings from the Rijksmuseum - Hirayama, Airi; Abe, Yoshinari; van Loon, Annelies; De Keyser, Nouchka; Noble, Petria; Vanmeert, Frederik; Janssens, Koen; Tantrakarn, Kriengkamol; Taniguchi, Kazuo; Nakai, Izumi (Microchemical Journal, 2018)
A portable X-ray powder diffractometer (p-XRD) PT-APXRD III has been developed for on-site analysis of paintings and archaeological samples. By using a Cu anode X-ray tube and a silicon drift diode (SDD) detector, diffraction patterns with a high signal-noise (S/N) ratio can be recorded. The X-ray tube can be operated at a maximum voltage of 60kV, which makes it possible to simultaneously record X-ray fluorescence spectra up to the high-energy region. The total weight of this instrument is 16kg, which can be carried anywhere and the goniometer unit (5.6kg) can be placed on a tripod for analysis of mural paintings. We brought the instrument to the Rijksmuseum in the Netherlands to examine its applicability for the analysis of oil paintings. We successfully analyzed two seventeenth-century oil paintings by Johannes Vermeer and Jan Davidsz de Heem (copy after). Ultramarine blue, lead-tin yellow type I, and Naples yellow were identified from the diffraction patterns, demonstrating the high practicality of this instrument. Furthermore, it was found from the SEM-EDX analysis of a paint cross section that the yellow pigment was applied in separate layers rather than being mixed. This diffractometer will be commercially available in the near future and will have many applications in the field of material analysis. •A new portable XRD suitable for analysis of paintings has been developed.•The total weight is 16kg and the goniometer (only 5.6kg) can be placed on a tripod.•The instrument also has a function of X-ray fluorescence spectrometer.•We revealed secrets of the use of pigments in 17th C oil paintings at Rijksmuseum.•This field portable diffractometer has unlimited application fields in material analysis.